2009
DOI: 10.1016/j.intmar.2009.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Does Chatter Matter? The Impact of User-Generated Content on Music Sales

Abstract: Abstract:The Internet has enabled the era of user-generated content, potentially breaking the hegemony of traditional content generators as the primary sources of "legitimate" information.Prime examples of user-generated content are blogs and social networking sites, which allow easy publishing of and access to information. In this study, we examine the usefulness of such content, consisting of data from blogs and social networking sites in predicting sales in the music industry.We track the changes in online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
169
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(185 citation statements)
references
References 23 publications
6
169
1
9
Order By: Relevance
“…In addition, a growing body of research has explored the relationship between product quality and purchase intention in the context of ecommerce, and found that ratings (e.g., [15,20,27,74,89]), website quality [41], and the perceived credibility of electronic word-of-mouth messages [17] all positively impact purchase decisions. Moreover, the perceived valence and credibility of product recommendations have been shown to have a significant impact on purchase intention, across a variety of consumer goods [38].…”
mentioning
confidence: 99%
“…In addition, a growing body of research has explored the relationship between product quality and purchase intention in the context of ecommerce, and found that ratings (e.g., [15,20,27,74,89]), website quality [41], and the perceived credibility of electronic word-of-mouth messages [17] all positively impact purchase decisions. Moreover, the perceived valence and credibility of product recommendations have been shown to have a significant impact on purchase intention, across a variety of consumer goods [38].…”
mentioning
confidence: 99%
“…User generated content is essential for the sustenance of networking sites (Agichtein et al, 2008), has become integral to the tourism industry (O'Connor, 2008), and has been shown to impact positively upon music sales (Dhar & Chang, 2009). Online newspapers too are moving towards greater integration and 10 interactivity with their readership in seeking to utilise user-generated content alongside their professionally developed material (Hermida & Thurman, 2008;Thurman, 2008).…”
mentioning
confidence: 99%
“…A literatura relacionada ao BAB apresenta evidências de que qualidade do serviço (Parasuraman, Zeithaml, & Berry, 1988) e satisfação (Matos, 2011) (Dhar & Chang, 2009). …”
Section: A Multidimensionalidade Do Babunclassified